PENERAPAN PEMBELAJARAN BERBASIS PROJEK PADA PERKULIAHAN PENDIDIKAN KIMIA UNTUK MENINGKATKAN KEMANDIRIAN DAN PRESTASI BELAJAR MAHASISWA - Antuni Wiyarsi; Crys Fajar Partana (PAEDAGOGIA, 2009)
This research aims to reveal (1) the effectiveness of Project-Based Learning viewed from student's autonomy in designing project, (2) the effectiveness of ProjectBased Learning viewed from student's collaborative efforts in finishing project, and 3) Project-Based Learning application based on the mastery of student's psychomotor aspect in Chemistry Education Workshop subject of study program of Chemistry EducationofDepartmentofChemistryEducation,FacultyofMathematicsandSciences, Yogyakarta State University. Subject of this research included students taking education workshop subject in semester 2 of academic year 2006/2007. There were 53 students divided into 7 groups. The research was designed as Classroom Action Research (CAR) with research steps referring to Kemmis and Mc Taggart model and conducted for 2 cycles.Datawerecollectedbypreliminarytestforstudent'spreliminarycapability,sheet of assessment for chemistry learning media design, sheet of observation for cooperation inmakingmedia,sheetofassessmentforpsychomotorandsheetofassessmentformedia. The result of the research showed that there was an increasing number of groups which have 'good' level in cycle 2 compared to cycle 1 in term of capability of media design, collaboration,assessmentforpsychomotorandmedia.